Quantitative summer and winter temperature reconstructions from pollen and chironomid data between 15 and 8 ka BP in the Baltic–Belarus area. (19th November 2015) - Veski, Siim; Seppä, Heikki; Stančikaitė, Migle; Zernitskaya, Valentina; Reitalu, Triin; Gryguc, Gražyna; Heinsalu, Atko; Stivrins, Normunds; Amon, Leeli; Vassiljev, Jüri; Heiri, Oliver
Abstract: New pollen based reconstructions of summer (May-to-August) and winter (December-to-February) temperatures between 15 and 8 ka BP along a S–N transect in the Baltic–Belarus (BB) area display trends in temporal and spatial changes in climate variability. These results are completed by two chironomid-based July mean temperature reconstructions. The magnitude of change compared with modern temperatures was more prominent in the northern part of BB area. The 4 C° winter and 2 C° summer warming at the start of GI-1 was delayed in the BB area and Lateglacial maximum temperatures were reached at ca 13.6 ka BP, being 4 C° colder than the modern mean. The Younger Dryas cooling in the area was 5 C° colder than present, as inferred by all proxies. In addition, our analyses show an early Holocene divergence in winter temperature trends with modern values reaching 1 ka earlier (10 ka BP) in southern BB compared to the northern part of the region (9 ka BP).